Personal Information Management (PIM) of academic researcher / Rahayu Handan - Handan, Rahayu (2012)
Personal Information Management (PIM) is about having the correct information in the correct place, in the correct form, and of adequate fullness and excellence to meet human present need. Better PIM means a better quality to our lives (individual or organization) and improves in education programs of information literacy. Hence, the aim of this study is propose strategies to tackle the issues of handling PIM activities task of academic researchers towards the improvement of information literacy among them. Therefore, PIM activities task within the context of academic researchers will be identified and followed by identifying the issues of handling PIM activities task while searching and managing found information. This paper reported the results of semi-structured interview using qualitative method of case study fifteen academic researchers within the scope of searching information on Web 2.0. This study discovered three main preferences of creating information using search engines, website and electronic journals. For saving, organizing and managing found information, most of them reported keeping their information in internal hard drive, external hardisk, and organize it by folders. With regard of retrieving information on the web, commonly they looked on their written note book before start retrieving. Email was the favourite option for distributing information. Categories of issues were derived from the semi-structured interview and literature analysis. Through content analysis, three strategies were identified to tackle the issues of handling PIM. These results extended the understanding of academic researchers' PIM behaviours; help inform the strategy of searching and strategy of managing using PIM digital tools.